0311 The Impairments in Emotional Perception Following Total Sleep Deprivation and the Restorative Effects of Napping and Time of Day. (27th May 2020) - Cunningham, T J; Bottary, R M; Kensinger, E A; Stickgold, R
Abstract: Introduction: The ability to perceive emotions is a socially-relevant skill critical for healthy interpersonal functioning, while deficits in this ability are associated with psychopathology. Total sleep deprivation (TSD) has been shown to have deleterious effects on emotion perception, yet the extent to which these impairments persist across the day with continued wakefulness, or if brief periods of recovery sleep can restore emotion perception abilities, remains unexplored. Methods: Participants viewed slideshows of faces ranging in emotional expression and were asked to categorize (Happy, Sad, Angry, Neutral) and rate the emotional intensity (1-9) of each face at baseline (2100; Session 1), at 0900 (Session 2) following a night of sleep or TSD, and at 1400 (Session 3) following either continued wakefulness (wake group) or a 90-minute nap opportunity (nap group). Results: Emotion categorization ability marginally improved from Session 1 to Session 2 following overnight sleep, however, no changes in emotion intensity ratings or vigilance were observed. TSD led to an increase in error rates during vigilance testing [t(46)=2.9, p=0.005] and impairment in emotion categorization ability [t(46)=5.5, p<0.001] from Session 1 to Session 2, although by Session 3 performance levels on both measures returned to baseline for all TSD participants. TSD also led to a decrease in emotional intensity ratings from Session 1 to Session 2, particularly for the highest tertile of emotional faces [6-9; t(46)=6.1, p<0.001]. These ratings remained suppressed at Session 3 in both the wake [t(25)=7.8, p<0.001] and nap [t(18)=3.1, p=0.006] groups. Conclusion: These results indicate that time of day effects, with or without any additional benefit of a nap, can restore the impairments in vigilance and emotional categorization caused by TSD. The ability to discriminate levels of emotional intensity, however, is not restored by time of day or napping, suggesting that this ability is more sensitive to the impact of TSD. Support: